2003
DOI: 10.1136/heart.89.12.1445
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment using the short form 12 questionnaire is as reliable and sensitive as the short form 36 in distinguishing symptom severity in myocardial infarction survivors

Abstract: F rom the patient's perspective, disease severity is gauged by its impact on health related quality of life (HRQL), whereas medical practitioners tend to focus on clinical parameters such as symptoms, signs, and investigations. HRQL assessment can complement clinical evaluation but has not been widely incorporated into routine clinical practice, perhaps because of an association with research, lack of familiarity, difficulties with data interpretation, or concern that outpatients is busy enough.The short form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 5 publications
1
34
0
5
Order By: Relevance
“…A similar decrement of physical functioning has been observed in chronic medical conditions such as chronic obstructive pulmonary disease 17 and survivors of myocardial infarction. 18 Patients also completed a health rating scale ranging from 0 to 100, with 0 indicating death and 100 indicating perfect health. The mean score was 79.61.…”
Section: Resultsmentioning
confidence: 99%
“…A similar decrement of physical functioning has been observed in chronic medical conditions such as chronic obstructive pulmonary disease 17 and survivors of myocardial infarction. 18 Patients also completed a health rating scale ranging from 0 to 100, with 0 indicating death and 100 indicating perfect health. The mean score was 79.61.…”
Section: Resultsmentioning
confidence: 99%
“…The validity and reliability of SF-12 have been evaluated in previous studies. Melville reported that SF-36 provides important quantitative information about the impact of diseases on health related quality of life [33] and Gandek reported that its internal consistency reliability was 0.83 to 0.93 for the eight scales and 0.94 and 0.89, respectively, for the physical and mental component summary measures [34].…”
Section: Methodsmentioning
confidence: 99%
“…The literature suggests that quality of life is impaired many years after MI for those with persisting symptoms, 180 the effect being more marked in younger than older people. The same is reported for those with non-cardiac chest pain.…”
Section: Baseline Analysismentioning
confidence: 99%